2001
DOI: 10.1046/j.1365-3083.2001.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of TCRα and β Chains from Human T‐Cell Clones Specific for Small Nuclear Ribonucleoprotein Polypeptides Sm‐D, Sm‐B and U1–70 kDa: TCR Complementarity Determining Region 3 Usage Appears Highly Conserved

Abstract: Systemic lupus erythematosus (SLE) and mixed connective tissue disease (MCTD) are systemic autoimmune diseases that are characterized by the presence of autoantibodies reactive with U small nuclear RNP (snRNP) autoantigens. Both B and T cells are important in the pathogenesis of the disease, and T-and B-cell immunity against snRNP polypeptides have been shown to be linked in vivo. Currently, several alternative hypotheses for the pathogenesis of these diseases have been proposed. These include loss of toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 31 publications
5
22
0
Order By: Relevance
“…Consistent with our previous results describing highly restricted complimentarity-determining region 3 usage by anti-U1-70kDa clones, a limited number of T cell epitopes were observed in the anti-U1-70kDa response (14). Remarkably, this response was exclusively limited to epitopes within the RBD of the molecule (residues 92-202), consistent with results previously reported in an animal model of systemic autoimmunity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our previous results describing highly restricted complimentarity-determining region 3 usage by anti-U1-70kDa clones, a limited number of T cell epitopes were observed in the anti-U1-70kDa response (14). Remarkably, this response was exclusively limited to epitopes within the RBD of the molecule (residues 92-202), consistent with results previously reported in an animal model of systemic autoimmunity.…”
Section: Discussionsupporting
confidence: 92%
“…We also reported that U1-70kDa-reactive T cells have a typical Th phenotype and produce cytokines that are important in B cell help and differentiation, including IFN-␥, IL-4, and IL-2 (13). Additionally, we have shown that TCR usage by U1-70kDa reactive T cells is highly restricted and by analysis of complimentarity-determining region 3 deduced amino acid sequences found a pattern characteristic of an Ag-driven immune response (14). Finally, in the MRL/Mp-lpr murine model of lupus, we have found that tolerization with a U1-70kDa fusion protein delayed the development of anti-snRNP Abs (15).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Defining whether a restricted or a broad family of TCRs is implicated in this mechanism will be also highly informative, because apparently there is an important difference between murine and human lupus with regard to the recognition of peptide P140 by CD4 ϩ T cells. It will be interesting to compare the data with those obtained with U1-70K protein-reactive human T cell clones, the TCR CDR3 of which have been sequenced and found to be highly conserved (37).…”
Section: Discussionmentioning
confidence: 99%
“…Both can help B cells to produce autoantibody but their role in effecting organ injury is not well understood. It appears that certain T cell clonotypes are involved in this process [12], suggesting strongly that limited autoantigens are responsible for the initiation of the autoimmune process. The ability of expanded T helper cells able to provide help to B cells has been exploited in clinical trials where the CD40-CD40 ligand cognate B-T cell interaction is disrupted with appropriate biologics [13].…”
mentioning
confidence: 99%